ANALISIS BIAYA RELEVAN DALAM PENGAMBILAN KEPUTUSAN MENERIMA ATAU MENOLAK PESANAN KHUSUS PADA CV. MANGUNI PERKASA - Raap, Gabriel Michele Margaretha; Saerang, David P.E; Pusung, Rudy J. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2014)
The success of an enterprise depends on the ability of corporate management in running the company. Decision making is one of the functions of a manager. In carrying out the activities of a company, the management is often faced with several options or alternatives of activities undertaken. To choose one of these alternatives the management need information about costs. The purpose of this study was to determine the cost of production cost calculations used by the company, as well as analyzes of relevant costs in relation to accept or reject a special order. The method used in this research is descriptive method. Based on the results of the study, showed that CV. Manguni Perkasa not applying relevant cost analysis method in calculating the cost of production. With the price of Rp 183.6 million special orders may be seen to be detrimental to the company that basically sells the house on stilts with the normal price of Rp 216 million, but when analyzed again using the relevant cost calculation method as a way to calculate the variable costs separately from the cost of production using the full costing method, the special orders stilt houses with a selling price of Rp 183.6 million is acceptable. Due to special order the sale price is greater than the variable costs incurred by the company in producing the stage.